Digital Health Literacy and Healthy Lifestyle Behaviors Among Migrant University Students Living in Boarding Houses Near Campus - Annisa Fitri Nasution; Mahfuzi Irwan; Mita Aulia; Chintia Mentari (CV. Eracita Grup, 2025)
This study aims to analyze the level of digital health literacy among migrant students living in boarding houses near campus and its association with healthy lifestyle behaviors. This study employed a quantitative approach using a survey design. Data were collected from migrant university students residing in boarding houses through a questionnaire based on the digital health literacy framework, encompassing four core dimensions: access, understand, appraise, and apply. Descriptive statistical analysis was used to examine patterns of digital health literacy and health-related behaviors. The findings indicate that most students demonstrate strong abilities in accessing and understanding digital health information, particularly through the internet and social media platforms. Students also show a relatively high level of awareness in verifying health information sources. However, a proportion of respondents remain uncertain when appraising the credibility of digital health information. In terms of application, the majority of students report engaging in positive health behaviors, including maintaining personal and environmental hygiene, regulating diet and hydration, performing light physical activity, and adopting adaptive coping strategies to support mental health. This study concludes that digital health literacy plays a significant role in shaping healthy lifestyle behaviors among migrant university students. Strengthening evaluative and applicative competencies through targeted digital health literacy education and campus-based health promotion programs is essential to support sustainable health behaviors in the digital era.